Monetary Policy Shocks and Portfolio Choice - Marcel Fratzscher; Christian Saborowski; Roland Straub (European Central Bank (ECB), 2009)
The paper shows that monetary policy shocks exert a substantial effect on the size and composition of capital flows and the trade balance for the United States, with a 100 basis point easing raising net capital inflows and lowering the trade balance by 1% of GDP, and explaining about 20-25% of their time variation. Monetary policy easing causes positive returns to both equities and bonds. Yet such a monetary policy easing shock also induces a shift in portfolio composition out of equities and into bonds, implying a negative conditional correlation between flows in equities and bonds. Moreover, such shocks induce a negative conditional correlation between equity flows and equity returns, but a positive conditional correlation between bond flows and bond returns. The findings thus provide evidence for the presence of a portfolio rebalancing motive behind investment decisions in equities, but the dominance of what is akin to a return chasing motive for bonds, conditional on monetary policy shocks. The results also shed light on the puzzle of the strongly time-varying equity-bond return correlations found in the literature.
Keywords: F4; E52; G1; F32; 330; asset prices; Capital flows; monetary policy; Portfolio Choice; sign restrictions; trade balance; United States; vector auto regressions; Geldpolitik; Kapitalmobilität; Handelsbilanz; Portfolio-Management; VAR-Modell; USA